20 años de la comercialización mundial de cultivos biotecnológicos - Garro-Monge, Giovanni (2016)
The use of living organisms to obtain goods and services for humans is known as biotechnology. From these improvements are achieved such as higher nutritional quality, drought tolerance, pest resistance, and more. This article describes that at the celebration of the twentieth anniversary of transgenic crops worldwide, it has been a success and the benefits obtained by farmers during these 20 years are estimated at a rather high figure but the use of transgenesis for the modification Of crops of commercial interest, has had a very negative response by society.